Asylum seekers' mental health and treatment utilization in a three months follow-up study after transfer from a state registration-and reception-center in Germany - Nikendei, Christoph; Kindermann, David; Brandenburg-Ceynowa, Hannah; Derreza-Greeven, Cassandra; Zeyher, Valentina; Junne, Florian; Friederich, Hans-Christoph; Bozorgmehr, Kayvan (Health policy, 2019)
Even though asylum seekers show a high prevalence of trauma-related disorders and comorbid psychological stress symptoms, little is known about how their mental health develops during the asylum process and what options of care are provided. We aimed to investigate the mental health and treatment utilization of asylum seekers after they were transferred from a state registration- and reception-center to municipal shelters in Germany. N = 228 asylum seekers with on-going asylum procedure were recruited in the psychosocial walk-in clinic located in a state registration- and reception-center. We firstly captured symptoms of posttraumatic stress, depression, anxiety disorders, quality of life, as well as alcohol or drug abuse. Subsequently we performed a follow-up after three months to evaluate a potential shift in symptoms and determining rates of access to treatment. In the pre-post psychometric assessment, there were statistically significant changes in depression (PHQ-2), panic (PHQ-PD) and psychosocial well-being scores (WHO-5). However, all these scores still remained within a clinical relevant range, respectively. Traumatic stress (PC-PTSD-5) and general anxiety scores (GAD-2) did not change significantly. Although N = 44 (66%) of the interviewed patients had been referred to psychotherapy initially, none (0%) of them had received outpatient psychotherapeutic treatment after three months. Our results emphasize a strong need for low-threshold, cultural adapted psychotherapeutic treatment for asylum seekers.